Facies association and depositional environment of fan-delta sequence in southwest Kathmandu Basin, Nepal - Tamrakar, Naresh Kazi; Shrestha, Pramila; Maharjan, Surendra (Bulletin of the Department of Geology, 2009)
Lake marginal sedimentation prevailed around the Paleo-Kathmandu Lake. Owing to the difference in local basin conditions; tectonics, source rock types and river systems therein, the lake marginal environments and sedimentary facies associations differ around the Paleo-Kathmandu Lake. In this study, the basin-fill sediments of southwestern margin of the Kathmandu Basin were studied for the sediments recorded in vertical sequences at various localities and facies analysis was made. Mainly eight facies were recognised. They were matrix-supported massive gravel (Gmm), matrix-supported graded gravel (Gmg), gravelly fine or mud (GF), massive silt (Fsm), massive mud (Fm), ripple-laminated silt or laminated silt/mud/clay (Fl), carbonaceous clay (C), and incipient soil with roots (Fr). Four facies associations that were identified were proximal fan-delta facies association (FA1), mid fan-delta facies associaiton (FA2), distal fan-delta facies association (FA3), and gravelly sinuous river facies association (FA4). Remarkably, these facies associations do not contain any sandy facies and foreset bedding of Gilbert-type. The fan-delta region was characterised by flood-dominated flows and vertical accretion of fines in the flood basins, and vegetated swamps rich in organic sediments. The distribution of facies associations suggests extensive lake transgression followed by rapid lake regression. The recent river system then incised the valley against local upliftment due to faulting or lowering of base level of the main river in the Kathmandu Basin probably related to draining out of the lake water. doi: Bulletin of the Department of Geology, Vol. 12, 2009, pp. 1-16